The Emerging Role of Neutral Argon Plasma (PlasmaJet) in the Treatment of Advanced Stage Ovarian Cancer: A Systematic Review. (June 2020) - Prodromidou, Anastasia; Pandraklakis, Anastasios; Iavazzo, Christos
Objective . To evaluate the contribution of PlasmaJet application in achieving optimal cytoreduction in advanced ovarian cancer. Methods . We systematically searched for articles published up to June 2019 using MEDLINE, Scopus, Google Scholar databases and clinicaltrials.gov along with the references of the articles retrieved in full text. Observational studies and case reports addressing cases of women with peritoneal spread due to advanced stage ovarian cancer who were treated with application of PlasmaJet device were considered eligible for inclusion. Results . Three studies were excluded from further analysis when they were retrieved in full text. Five studies (2 retrospective, 1 prospective, and 2 case reports) that comprised 77 patients with age range from 38 to 85 years were included. Forty-three women underwent interval debulking surgery, 24 patients primary debulking surgery, and 6 had optimal debulking surgery, while in the remaining 4, a secondary debulking surgery was performed. Incidence of intraoperative complications was 32% (8/25), but none of them was due to the application of PlasmaJet. Complete macroscopic resection was achieved in 59 out of 70 (84.3%) women. Postoperatively, 17 out of 72 patients (23.6%) developed complications such as pneumothorax due to diaphragmatic resection, systemic infections, or wound-related complications. No postoperative mortality was recorded. Conclusions . Preliminary data on the use of PlasmaJet for ablation of ovarian cancer implants in the peritoneal cavity showed its safety and presented with promising outcomes in achieving complete cytoreduction.